1983
DOI: 10.1037/0021-9010.68.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Statistical power of tests of the situational specificity hypothesis in validity generalization studies: A cautionary note.

Abstract: This study, using Monte Carlo simulation techmques, evaluated the statistical power of the Callender-Osburn method for testing the situational specificity hypothesis in validity generalization studies. In addition, the Schmidt-Hunter 75% rule for testing the situational specificity hypothesis was studied with regard to its sensitivity for detecting both Type I and Type II errors The results showed that both the Callender-Osburn procedure and the Schmidt-Hunter 75% rule lacked sufficient statistical power to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
1

Year Published

1985
1985
1994
1994

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 11 publications
1
62
1
Order By: Relevance
“…This can be solved only by doing more primary studies. The good news is that power may be less of a problem in meta-analysis than in primary research (Osburn, Callender, Greener, & Ashworth, 1983;Sackett, Harris, & Orr, 1986;Spector & Levine, 1987). The reason is that the unit of analysis in primary research is usually an individual, but the unit in meta-analysis is a study-level effect size that is an aggregate of these primary units.…”
Section: Problems With Analyzing Moderator Effectsmentioning
confidence: 99%
“…This can be solved only by doing more primary studies. The good news is that power may be less of a problem in meta-analysis than in primary research (Osburn, Callender, Greener, & Ashworth, 1983;Sackett, Harris, & Orr, 1986;Spector & Levine, 1987). The reason is that the unit of analysis in primary research is usually an individual, but the unit in meta-analysis is a study-level effect size that is an aggregate of these primary units.…”
Section: Problems With Analyzing Moderator Effectsmentioning
confidence: 99%
“…In the interest of fairness, we believe that it is important also to evaluate the power of the VG ratio in regard to rejecting the null hypothesis of situational specificity. A recent simulation study by Osburn et al (1983) suggested that the decision rule to reject the situational specificity hypothesis when 2/ 2 >.75 results in too much power in the sense that situational specificity is rejected when low to moderate variance exists among the pi (true validities), given that the n are not large (< 100). We wish to address this point with some logic and simple algebra within the context that sample sizes are not large (e.g., .i 70) and for the critical value of the VG decision rule (i.e., > .75).…”
mentioning
confidence: 99%
“…In studies where the variance in true validities remains substantial after removing artifactual variation, the lower limits of the credibility interval is used to justify conclusions about the generalizability of the test' validity across settings and organizations (Osbum, Callender, Greener, & Ashworth, 1983;Pearlman et al, 1980;Schmidt ~z Hunter, 1981;Schmidt, Hunter, & Pearlman, 1982;Schmidt et al, 1979;Schmidt, Pearlman, Hunter, & Hirsh, 1985). As described in Schmidt and Hunter (1977), the credibility interval is to have a Bayesian interpretation as an interval centered at the mean of the posterior distribution of true validities.…”
mentioning
confidence: 98%